THE SIGNIFICANCE OF THE DEVELOPMENT OF TRANSPORT LOGISTICS IN THE CUSTOMS SYSTEM AND THE DIRECTIONS OF ITS DEVELOPMENT (Marketing Journal, 2025)
336 This article examines the pressing issues of developing transport and logistics infrastructure within the customs system, particularly focusing on ensuring the safety and efficiency of cargo transportation through the use of modern technologies such as electronic seals. Based on international experience, the need to enhance logistics efficiency, strengthen integration between customs and other government agencies, and implement digital monitoring systems is substantiated. The statistical analysis of Uzbekis tanʼs foreign trade cargo movement highlights the growth trend in road transportation and the simplification of customs procedures. The article concludes with practical recommendations for sectoral development.
Keywords: customs logistics; transport -logistics system; electronic seal; international trade; cargo transportation; transit; digitalization; customs control; logistics infrastructure; integration